Implementation of Failover in a Master-Slave Architecture for Soil Moisture Sensor Data Transmission - Ajeng Fitria; Uray Ristian; Syamsul Bahri; Ida Bagus Gede Sarasvananda (Jurnal Media Informasi Teknologi, 2026)
Development of Internet of Things (IoT) offers significant opportunities in the agricultural sector by enabling automatic and efficient monitoring of crop conditions. A common issue in IoT-based monitoring systems utilizing a master-slave architecture is the loss of data communication when the master node experiences a failure, which reduces system reliability. This research develops a plant monitoring system based on a master-slave architecture with a failover method using ESP32 and HTTP communication. The system consists of three master nodes, each handling two slave nodes, with a total of twelve soil moisture sensors. Data from the sensors are transmitted by the slave nodes to the master nodes, then forwarded to a cloud server. The failover method functions to maintain communication continuity by rerouting data transmission when a master node experiences a failure. The test results show that the system without failover experienced data loss and communication downtime equal to the duration of the master node failure, while the integration of IoT and failover method maintained communication with an average packet loss of 2.22% and a switching delay of approximately 0.78 seconds.